The Role of Celebrity Endorsements, Electronic Word of Mouth, and Product Placement on Purchasing Decisions - Purwanto, Agus; Aqila Praditya, Rayyan (AGUSPATI RESEARCH INSTITUTA, 2024)
This research aims to determine the influence of Celebrity Endorsement, Electronic Word Of Mouth, and Product Placement on Purchasing Decisions. This research is quantitative research conducted on consumers. Sample this research consisted of 567 respondents who were determined using the purposive sampling method. Data collection in this research used a questionnaire instrument distributed via Google Forms. The data analysis technique uses path analysis with the partial least squares structural equation modeling (PLS-SEM) method with data processing tools using Smart-PLS 3.0 software. Questionnaire is closely designed, except for the questions/statements concerning the respondent’s identity, which is a semi-opened questionnaire. Every closed questions/statement, five answer options is given in Likert scale, which consist of: strongly agree (SA) with 5 scores, agree (A) with 4 scores, Neutral (N) with 3 scores, disagree (DA) with 2 scores, and strongly disagree (SDA) with 1 score. The method in data processing is by using PLS and SmartPLS 3.0 software as the tool. The results of the research show that Celebrity Endorsment, Electronic Word Of Mouth, and Product Placement have a positive effect and significant to Purchasing Decisions.